The correlation between expression of sip protein in different serotypes of group b streptococcus and diagnosis. Issue 6 (June 2019) - Cheng, Shiliang; Han, Jiae; Huang, Yidan; Yan, Qin; Lu, Gang; Yuan, Zuowei; Huang, Guanjun; Zheng, Jian; Liu, Tianqiang
Abstract: Since the surface immunogenic protein (Sip) of group B streptococcus was identified, it's immunogenicity and its potential as a universal vaccine candidate has been evaluated extensively. We developed recombinant Sip protein and used it for monoclonal antibody generation to develop immunochromatographic test kit for GBS detection. The test of bacteria and culture media revealed the correlation between Sip protein expression and diagnosis discrepancy, which has never been reported. Furthermore, not only the surface accessibility of the Sip protein may vary from strains or serotypes; the secretion level of Sip protein may also vary.